Survival prediction among pathologic T4 bladder cancer patients following cytoreductive cystectomy: A retrospective single-center study - Bai, Xuesong; Chen, Guo; Shang, Shihai; Li, Senlin; Liu, Huanrui; Feng, Zhenwei; Gou, Xin (Frontiers in Surgery, 2023)
Objectives: This retrospective study aimed to describe our institutional experience with cytoreductive/palliative cystectomy (Cx) in patients with pathological T4 (pT4) bladder cancer (BCa) and to investigate clinicopathologic factors that predict patient survival outcomes. Methods: We reviewed the baseline demographics, clinicopathologic features, perioperative complications, and follow-up data of 44 patients who underwent Cx for pT4 BCa at our institution between 2013 and 2021. The Kaplan–Meier method was compared with the log-rank test to analyze progression-free survival (PFS) and overall survival (OS). Univariate and multivariate analyses were performed using the Cox regression model. Results: Median age of the patients was 68 years (95% confidence interval [CI] 49−81). Overall, 21 patients (47.7%) were estimated to have a high age-adjusted Charlson comorbidity index (ACCI) score (>4), and nine patients (20.5%) had pT4b BCa. None of the patients died of complications within 30–90 days. Severe complications occurred in 16 % (n = 7) of patients within 30–90 days. During a median follow-up of 51 months, disease progression was detected in 25 patients (56.8%), and 29 patients (65.9%) died of any cause. The median PFS and OS was 15.0 and 21.0 months, respectively. Kaplan–Meier analysis indicated that patients with high ACCI scores or pT4b BCa had worse PFS (P= 0.003 and P= 0.002, respectively) and OS (P = 0.016 and P=0.034, respectively) than those with low ACCI scores or pT4a BCa. On multivariate analysis, pT4b substage (hazard ratio [HR], 4.166; 95% CI, 1.549–11.206; P = 0.005) remained an independent risk factor for PFS and ACCI score > 4 (HR, 2.329; 95% CI, 1.105–4.908; P = 0.026) for OS. Conclusion: Our study revealed that pT4b substage is associated with poor prognosis and that the ACCI score is a relevant and practical method to evaluate survival outcomes in patients with pT4 BCa after Cx.